Soluble programmed cell death protein-1 and programmed cell death ligand-1 in sepsis - Banerjee, Debasree; Monaghan, Sean; Zhao, Runping; Walsh, Thomas; Palmisciano, Amy; Phillips, Gary S.; Opal, Steven; Levy, Mitchell M. (Critical care (London, England), 2018)
Immunotherapy targeting the programmed cell death protein-1 (PD-1)–programmed cell death ligand-1 (PDL-1) axis in sepsis is poised for clinical trials, although optimal inclusion criteria and predictors of response are not well characterized. Soluble PD-L1 outperforms sPD-1 for discrimination of sepsis Table 1 Patient characteristics Variables Septic patients (n = 30) Control subjects (n = 30) Age (years), median (IQR) 63.3 (49.3–74.1) 58.6 (52.8–64.6)  Male, n (%) 11 (36) 19 (63)  White, n (%) 23 (76) 25 (83) Past medical history  COPD/asthma/fibrosis, n (%) 11 (36) 2 (7)  CAD/MI, CHF, AF, n (%) 16 (53) 7 (23)  Diabetes mellitus, n (%) 5 (17) 10 (33)  Malignancy, n (%) 8 (27) 6 (20)  CKD/ESRD, n (%) 5 (17) 1 (3)  Cirrhosis, n (%) 0 (0) 4 (13)  Connective tissue disease, n (%) 3 (10) 0  Arthritis, n (%) 3 (10) 3 (10) Clinical assessment  WBC (×10−9/L), median (IQR) 12.8 (6.9–19.1) 9.1 (7.6–10.9) SOFA score, median (IQR) 7 (5–9) 2 (1–4)  Shock, n (%) 24 (80) 2 (6) Site of infection in septic patients (n) Pneumonia 13 Genitourinary tract infection 11 Abdominal infection 2 Meningitis 1 Multiple sites of infection 1 Bacteremia 9 Unknown 1 Organism of infection if known in septic patients (n)  Escherichia coli not extended-spectrum β-lactamase producer 4  Escherichia coli extended-spectrum β-lactamase producer 2 Enterobacter 1  Enterococcus faecalis 1  Acinetobacter baumannii 1  Pseudomonas aeruginosa 1  Methicillin-resistant Staphylococcus aureus 1  Methicillin-sensitive Staphylococcus aureus 1  Candida albicans 1  Haemophilus influenzae 1 Bacillus species not anthracis 2  Klebsiella pneumoniae 1 AF atrial fibrillation, COPD chronic obstructive pulmonary disease, CAD coronary artery disease, CHF congestive heart Failure, CKD chronic kidney disease, ESRD end-stage renal disease, IQR interquartile range, MI myocardial infarction, SOFA sequential organ function assessment, WBC white blood cell Figure 2 Fig. 2 Correlation between soluble programmed death protein-1 (sPD-1) and soluble programmed death ligand-1 (sPD-L1) on day 0 among all ICU patients. Authors’ Affiliations (1) Departments of Medicine, Warren Alpert Medical School of Brown University, Providence, USA (2) Lifespan Hospital System, Providence, USA (3) Department of Surgery, Warren Alpert Medical School of Brown University, Providence, USA (4) Department of Biomedical Informatics, Center for Biostatistics, Ohio State University, Columbus, USA Chen Y, Li M, Liu J, Pan T, Zhou T, Liu Z, Tan R, Wang X, Tian L, Chen E, et al. sPD-L1 expression is associated with immunosuppression and infectious complications in patients with acute pancreatitis.